Geology of the Desaguadero and Bebedero Basins (Late Pleistocene-Holocene), San Luis, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The main purpose of this contribution is to present an updated vision of the knowledge of the Quaternary sedimentary successions and the first morphostratigraphic mapping of the central-west of San Luis province, at the distal eastern piedmont plain of the Cordillera de los Andes. These sequences are composed of deposits of fluvial, fluvial-lacustrine and alluvial-aeolian origin and their main outcrops are exposed in the central-western region of the San Luis province and the central-east sector of Mendoza province, in the Desaguadero River valley and the Bebedero depression (Fig. 1). The main geomorphological units of the area are the tectonic depressions known as depresión longitudinal central and depresión occidental, and the serranías occidentales hills (González Díaz, 1981), represented in the study area by the Cabras hill. The Desaguadero River valley is a notorious north-south elongated feature on the depresión occidental unit, with a main channel incised approximately between 3 and 11 meters into an older fluvial plain. The Bebedero depression is a subunit in the southern part of the depresión longitudinal central, interpreted as a fault-block basin (González, 1994) and structured at the east of the Desaguadero block (Ortiz et al., 1977) from the Diaguita tectonic event (late Pliocene). It contains the present day saline of Bebedero surface and paleoshores linked to the remarkable Late Pleistocene-Holocene expansion of an approximately 650 km2 paleolake, when the Desaguadero River and the Bebedero depression were connected from the south with the Bebedero Arroyo. The Bebedero depression and the Desaguadero River are separated by the Cabras hill and its underground continuity to the south in the Pencoso-Donado structural high, through a broad and very low slope piedmont covered by a mixed of alluvial and aeolian deposits. The Arco del Desaguadero Formation (Rodríguez y Barton, 1993) is the only Quaternary unit defined in the region and its typical sedimentary profile outcrops at the confluence of Jarilla Arroyo in the middle basin of the Desaguadero River. Here, the base of the Arco del Desaguadero Formation overlies an erosional unconformity carved on deposits which we attribute to lower to middle Pleistocene (Fig. 3). On the other hand, the sedimentary sequences present in the Bebedero depression have been linked to climatic events and piedmont deposits in the Cordillera de los Andes (González, 1981), but they have not been referred to any lithostratigraphic unit in particular. Considering stratigraphy, regional geomorphology, paleontological records of gastropods and charophytes, and new radiocarbon ages, we propose three lower-level units composing the Arco del Desaguadero Formation, namely: Salina del Bebedero Member (late Pleistocene), Río Desaguadero Member (early to middle Holocene) and Dos Anclas Member (late Holocene) (Table 1; Fig. 2). The Salina del Bebedero Member is a fluvial succession dominated by sandy gravels (high-energy environment) as in saline of Bebedero paleoshores (Figs. 4, 5) and silty sands (moderate-energy environment) as the ones at the basal strata on the Desaguadero River banks (Figs. 6-8). They present gray to brown yellowish-reddish colors and, at the saline of Bebedero paleoshores, have radiocarbon dates of 20.140 ± 170 y 14C BP (23.963-24.368 cal yr BP) and 15.280 ± 200 y 14C BP (18.283-18.723 cal yr BP). The Río Desaguadero Member is characterized by a cyclicity of fluvial and lacustrine deposits outcropping in the arroyo Jarilla banks (Fig. 9), as well as identified in the core taken from the borehole drilled at the center of saline of Bebedero (Fig. 10). These deposits are dominated by silty sands with reddish brown, yellowish and greenish colors and isolated layers containing high concentrations of carbonate and gypsum of white and gray colors, whose radiocarbon ages are in the range between 10.700 ± 170 y 14C BP (12.180-12.743 cal yr BP) and 6.519 ± 54 y 14C BP (7.324-7.433 cal yr BP). The Dos Anclas Member represents a set of relatively thin outcropping deposits (less than 3 meters), but widely distributed in the region and with high variability of sediments, which suggest different depositional conditions (Fig. 11) such as the fluvial silts of the Tunuyán River paleochannel (Figs. 12-14), the evaporites of Bebedero depression, and the sandy silt of paleosoil and silty sands of floodplain units (Table 4). The radiocarbon ages range from 3.444 ± 54 y 14C BP (3.570-3.718 cal yr BP) to 930 ± 60 y 14C BP (731-904 cal yr BP). Paleontological record includes the presence of shells restricted to certain levels of the external paleoshore in the saline of Bebedero, Desaguadero River and paleochannels of Tunuyán River, from which radiocarbon datings were possible. We report the presence of the shells of the gastropods: Chilina mendozana, Heleobia parchappii, Biomphalaria peregrina, Succinea meridionalis (Fig. 15), the family Ancylidae, Lymnaeidae, Physidae and Pupillidae, as well as few specimens of the bivalves Pisidium chiquitanum and Musculium aff. patagonicum (Fig. 16). The gyrogonites of charophyta have their greatest representation in the strata of arroyo Jarilla and are recognized as Chara contraria, Chara cf. papillosa, Chara halina and Chara hornemannii (Fig. 17). The evolution of these sedimentary basins responds to climatic stages linked to the Last Glacial Maximum and the Holocene Postglacial, under the influence of a paleo-landscape generated by the effects of neotectonics. In this context, the Desaguadero regional fault in the depresión occidental and local faults southward of the Bebedero depression are the main structures (González, 1994). High-energy fluvial regimes during late Pleistocene in the region are expressed through the incision of early to middle Pleistocene deposits in the Desaguadero River basin and the expansion of the Bebedero paleolake. This fluvial erosion originated the paleosurface where the Salina del Bebedero Member was deposited. During the early Holocene, probably related to the fluctuations of the Hypsithermal, sedimentary deposits in conditions of lower fluvial energy and local lacustrine bodies were developed (Río Desaguadero Member). The marked variability of late Holocene climatic conditions is manifested by restricted fluvial deposits, alluvial soil development, and aeolian sediments, all of them being encompassed by the Dos Anclas Member. Finally, during the last centuries, the region has suffered a climate crisis that characterizes the South American Arid Diagonal (Piovano et al., 2009), while the relationship between seismic events and strong river discharges has caused the retreat of headers and the incision of the Desaguadero River channel, as well as the desiccation of the lake and the development of the Bebedero saline
Keywords: Stratigraphy, Geomorphology, Paleontology, San Luis.